Islamic vs. Conventional Banking : Business Model, Efficiency and Stability - Beck, Thorsten; Demirgüç-Kunt, Asli; Merrouche, Ouarda (2012)
This paper discusses Islamic banking products and interprets them in the context of financial intermediation theory. Anecdotal evidence shows that many of the conventional products can be redrafted as Sharia-compliant products, so that the differences are smaller than expected. Comparing conventional and Islamic banks and controlling for other bank and country characteristics, the authors find few significant differences in business orientation, efficiency, asset quality, or stability. While Islamic banks seem more cost-effective than conventional banks in a broad cross-country sample, this finding reverses in a sample of countries with both Islamic and conventional banks. However, conventional banks that operate in countries with a higher market share of Islamic banks are more cost-effective but less stable. There is also consistent evidence of higher capitalization of Islamic banks and this capital cushion plus higher liquidity reserves explains the relatively better performance of Islamic banks during the recent crisis.